PROBLEMATIKA PELAKSANAAN PEMBERIAN BANTUAN HUKUM PADA TINGKAT PENYIDIKAN - Danadyaksa Putra; Nafi’uddin Fauzi Mahfudh (Sebelas Maret University, 2023)
This study aims to find out the the arrangement of the rights of suspects to receive legal aid in Indonesian positive law. In addition, it is also to find out the problems in the implementation of the provision of legal aid at the investigative level. The method used in this research is normative legal research which is prescriptive and applied. The approach that the author uses in this study is statute approach and conseptual approach. The types and sources of legal materials used are primary and secondary legal materials by means of literature/document studies. The law material analysis technique uses the syllogism method using a deductive mindset. Based on the results of the study, it was found that in principle the arrangements regarding the rights of suspects to receive legal aid at the investigation level have been regulated in such a way in various laws and regulations of the Republic of Indonesia. However, legal aid arrangements that have been arranged in such a way do not mean there are no problems in their implementation. The provision of legal aid at the investigation level, where the main arrangement is based on the provisions of Article 56 of the Criminal Procedure Code, there are still various problems in its implementation. The problem can be seen from the legal system, legal structure, and legal culture of the implementation of the provision of legal aid at this level of investigation.Keywords: Legal Aid; Investigation; Suspect